2022
DOI: 10.1038/s41427-022-00432-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic approach for enhancing superconducting critical current performance

Abstract: The addition of artificial pinning centers has led to an impressive increase in the critical current density (Jc) of superconductors, enabling record-breaking all-superconducting magnets and other applications. The Jc of superconductors has reached ~0.2–0.3 Jd, where Jd is the depairing current density, and the numerical factor depends on the pinning optimization. By modifying λ and/or ξ, the penetration depth and coherence length, respectively, we can increase Jd. For (Y0.77Gd0.23)Ba2Cu3Oy ((Y,Gd)123), we can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 61 publications
(107 reference statements)
1
22
0
Order By: Relevance
“…Above 20 K, S of the unirradiated sample deviates from its previous trend with further increasing T and has a minimum near 40 K, while the S values of the irradiated samples increase significantly with increasing dose (or total dpa). Introduction of non-superconducting nano defects is known to inhibit flux creep [34,35,37]. However, our data show a higher flux creep increases after the introduction of defects by irradiation.…”
Section: Resultsmentioning
confidence: 48%
“…Above 20 K, S of the unirradiated sample deviates from its previous trend with further increasing T and has a minimum near 40 K, while the S values of the irradiated samples increase significantly with increasing dose (or total dpa). Introduction of non-superconducting nano defects is known to inhibit flux creep [34,35,37]. However, our data show a higher flux creep increases after the introduction of defects by irradiation.…”
Section: Resultsmentioning
confidence: 48%
“…The main consequence of this reduced ratio is that the YBCO growth temperature is decreased and the superconducting properties improved due to the modified microstructure [31,53,57,[74][75][76][77]. Microstructural studies have shown that these non-stoichiometric compounds display a reduced porosity and a lower concentration of a/b nucleated crystals while the expected secondary phases (mainly Y 2 Cu 2 O 5 and CuO) do not perturb in a relevant way the epitaxial microstructure and so this modified metal stoichiometry has been widely used by many authors to grow CCs displaying very good superconducting performance [57,74,76,[78][79][80][81]. It is also worth to mention that the validity of the TFA approach has been widely proved for most of the Rare Earth compounds in REBCO films where high superconducting performances have been demonstrated [40,73,82].…”
Section: Low Fluorine Solution Synthesismentioning
confidence: 99%
“…It was shown that above a concentration of 10%-12% mol in the final YBCO layer there was a tendency towards NP aggregation and the size control of the NPs was compromised [90,91]. An alternative deposition approach was devised which hindered the NP diffusion and coarsening by taking advantage of the CuO interlayer formed at the intersurfaces of multideposited pyrolyzed films, called UTOC [40,[79][80][81]. This novel process selects ultrathin (∼30 nm) YBCO layers and a solution multideposition approach to reach competitive total film thickness and critical currents, for instance, 35 repetitions of the spin-coating/pyrolysis cycle were required to get a final film thickness of ∼0.6-0.7 µm [40,92].…”
Section: Np Preparation and Colloidal Solution Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stangl et al concluded that the condensation energy was increased by over-doping. Furthermore, by combining a thermodynamic approach with microstructural modification by BaHfO 3 nano particles, Miura et al reported on a record pinning force density F p of 3.17 TNm −3 at 4.2 K and 18 T (H ∥ c) for (Y,Gd)Ba 2 Cu 3 O 7−δ grown on technical substrate [74]. As shown in figure 5, T c is almost constant in a wide range of doping for NdFeAs(O,H), which is the most suitable system for the improvement of J c by heavy carrier doping.…”
Section: (B)) Whereas H C2 Of Ndfeas(oh) Is Comparable To That Of Ndf...mentioning
confidence: 99%